Investment Interest: Factors Affecting Investors in the Capital Market - Soleha, Erin; Lazuarni, Shafiera (Universitas Negeri Semarang, 2024)
Economic activity can increase with the existence of the capital market as an alternative funding for companies so they can expand their business more widely so that it will increase income. This research aims to determine the influence of income, investment knowledge and investment motivation on interest in investing in the capital market. This research was conducted on capital market investors in West Java Province. The sampling technique uses a non-probability sampling method with the Accidental Sampling technique because the population in West Java is unknown, so the formula needed to determine the sample size is to use the Lemeshow formula. So the minimum sample size required in this research is 100 respondents. In this research, questionnaires were the only data collection technique used. Meanwhile, the statistical test tool used in this research is SmartPLS. From the research that has been carried out, results have been obtained which show that income and investment motivation have an influence on interest in investing in the capital market and investment knowledge has no effect on interest in investing in the capital market. The results of this research explain that the amount of income one has and the high level of motivation will make someone interested in investing, while investment knowledge cannot yet determine whether someone is interested in investing in the capital market or not.